2022
DOI: 10.1007/s10578-022-01444-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents’ Internal Processes and Feelings Contribute to the way they Report Their Children’s Mental Difficulties on the Strength and Difficulties Questionnaire (SDQ)?

Abstract: The way parents report their child’s emotional and behavioral difficulties is important both for identifying the child’s needs, diagnosis, and prevention. This study examined to what extent parents’ internal processes predict the way in which parents report their child’s emotional and behavioral difficulties on the SDQ, as mediated by parental feelings. Parents of children who were referred to a community mental health clinic completed a self-report questionnaire including the following scales: adulthood attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…First, the same parent reported both their own expressivity and their children's prosocial behaviors in the present study. This may lead to common method variance; for example, parents with negative emotions may report both lower positive emotional expressivity and children's lower prosocial behaviors (Shenaar‐Golan & Hen, 2022), which could potentially bias the within‐person associations between parental expressivity and children's prosocial behaviors. Moreover, although the SDQ‐CV is a reliable and validated questionnaire for measuring children's prosocial behaviors (Liu et al., 2013), the small number of items and only parental reports may not comprehensively reflect prosocial behaviors in school‐aged children.…”
Section: Discussionmentioning
confidence: 99%
“…First, the same parent reported both their own expressivity and their children's prosocial behaviors in the present study. This may lead to common method variance; for example, parents with negative emotions may report both lower positive emotional expressivity and children's lower prosocial behaviors (Shenaar‐Golan & Hen, 2022), which could potentially bias the within‐person associations between parental expressivity and children's prosocial behaviors. Moreover, although the SDQ‐CV is a reliable and validated questionnaire for measuring children's prosocial behaviors (Liu et al., 2013), the small number of items and only parental reports may not comprehensively reflect prosocial behaviors in school‐aged children.…”
Section: Discussionmentioning
confidence: 99%
“…This method of data collection required a comprehensive analysis of the sociodemographic and clinical characteristics and psychosocial well-being of the mothers. This was performed to mitigate potential biases in the assessment of the children's psychosocial well-being, such as those arising from maternal depressive symptoms [52]. Further, the questionnaire was not amended after the onset of the pandemic with pandemic-related questions regarding the children.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…For instance, Booth et al (2023) found that parental psychological distress was associated with all SDQ scales, as adolescents reported higher difficulties and lower prosocial behavior if their parent had a higher level of distress. Recently the authors of this paper found that parental anger and sadness impacted parents' reporting on the SDQ (Shennar‐Golan & Hen, 2022). Using other multi‐informant measures, Maoz et al (2014) suggested the significance of maternal depression and mood changes to parental reporting.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have found that parental feelings are influenced by intrapersonal and interpersonal aspects, such as the parent's level of maturity, ability to regulate emotions, sense of self‐efficacy, and mental well‐being, as well as environmental aspects, such as education level, socioeconomic status, and the special needs of parents or children (Ziv et al, 2020). Studies focusing on parental feelings in the specific context of the parental role (e.g., Bradley et al, 2013; Fijałkowska & Bielawska‐Batorowicz, 2021; Shennar‐Golan & Hen, 2022), suggest three specific groups of feelings experienced by parents in their roles: anger (e.g., annoyance), anxiety/sadness (e.g., fear), and happiness (e.g., cheerfulness). Considering these studies and given that parents are responsible for managing their own feelings and helping their children manage their emotions, the importance of studying parental feelings continues to escalate (Teti & Cole, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation